VD_FINDINFO Jug / 2022 / 206 vom 24. August 2021 - VD Tribunal cantonal (2021)
AGRESSION, INJURE, VIOLENCE CONTRE LES AUTORITÉS, SURSIS À L'EXÉCUTION DE LA PEINE, PRÉSOMPTION D'INNOCENCE | 134 CP, 177 al. 1 CP, 285 ch. 1 CP, 34 CP, 40 CP, 47 CP, 49 al. 1 CP, 49 al. 2 CP, 51 CP, 69 CP, 10 CPP (CH), 135 CPP (CH), 386 al. 2 let. a CPP (CH), 423 al. 1 CPP (CH)